Does coping mediate the effect of financial threat on life satisfaction? A multigroup analysis - Matavelli, Rafaela Dias (2021)
Abstract: The year of 2007 was marked by one of the most severe global financial crises, which led to an increase of psychopathological symptoms that negatively affected life satisfaction. This research analyzed how financial threat was associated with life satisfaction and how coping, as a mediating variable, influenced this relationship. The theoretical model was tested through a sample of 901 Portuguese individuals, averaging 37 years old (SD=12.86). A structural equation modelling (SEM) was used to obtain the results, by using a multiple-group analysis. Overall, the results showed that financial threat is negatively associated with life satisfaction and that proactive coping strategies have a positive association with life satisfaction. The results obtained from coping as a mediating variable were not significant (considering the total sample). However, when we performed a multiple-group analysis, in the group of individuals with lower levels of financial threat, the mediation effect was statistically significant, showing an almost total attenuation of the crisis’s negative effects on life satisfaction. Thusly, we can infer that the mediating role of coping depends on the level of perceived financial threat. Since periods of financial threat have a negative impact on individuals’ psychological health, coping strategies can mitigate this relationship by decreasing the aforementioned negative impact.